A Sociolinguistic Analysis of English Borrowing in Selected Bangladeshi Films - Khan, Akibur Rahman; Akhter, Priyanka (International journal of multicultural and multireligious understanding, 2025)
This study explored the lexical and contextual nature of borrowed English into Bengali cinema (Films). For the exploration of the subject matter, the study examined five Bengali films based on purposive sampling. The researchers explored the films through Qualitative Comparative Analysis (QCA) and the exploration illustrated four types of lexicons, which were ‘words with Bengali equivalents’, ‘words without Bengali equivalents’, words with close Bengali equivalents’, and ‘hybridized words.’ The highest number of words were found from the category ‘words with Bengali equivalents’, which reflects the dominant feature of English lexicon over Bengali counterpart. The researcher also analyzed the contextual use of English in conversation of the films and found that the use of English is mostly in respect to showing power, dominance and reflecting social hierarchy.  The study helps to have a deeper look into the borrowing of English in Bengali films are their uses in different context.